PENGARUH PERSEPSI MASYARAKAT KOTA PEKALONGAN TERHADAP BANK SYARIAH - Moegiri Moegiri (Neraca, 2016)
This study aims to find out how the influence of education level, thi age, and service give effect on the puception of Pekalongan citizen to the sharia bank partially or jointly. The subject of this study is the Pekalongan citizen with the avarage age 20 years old at minimum, senior high school at education level, and at the job level, they consist of the students of university, military/ policeman/ goverment staff/ retired, the self employed the employees, and the house wife. The sample of this study took 100 people used nonprobability sampling method. In deciding the respondents, the writer used convinience sampling. Furthermore, selft administered survey was used a data collecting method. In this case, the respondents are asked to fill the questionaires by themselves, using excel program. This progam automatically would analyze the respondents characteristics. Besides, the writer used multiple linier regression analysis to his analysis technique, he used likers scala then it would be given the score. The software of SPSS was also used to manage the data meanwhile, the nonprobability analysis model of this study was used to analyze the citizens perception on the sharia bank in Pekalongan. Based on the research, it showed that the most factori which gives effect on the citizens perception of the sharia bank is the services given by the sharia banks to their customers.